Introducing Important Tax Provisions into Advanced Accounting. - Wojdak, Joseph F.; Crumbley, D. Larry; Mead, George C. (The Accounting Review, 1969)
Abstract The article discusses the significance of introducing important tax provisions into advanced accounting. Many accounting courses could be improved significantly by the brief introduction of related tax considerations, preferably in a non-technical fashion. This is particularly true in the case of advanced accounting courses wherein consolidated financial reporting for multi-entity organizations is usually given considerable attention. Decisions regarding the form of corporate and tax reporting for multi-entity organizations are highly tax-influenced. Tax planning is the art of determining in advance what tax liability will result and then conducting transactions with a view toward reducing the income tax burden. In the area of multiple corporations' a group has a choice of accomplishing the same results by more than one method-one of which may result in a lower tax liability. In order to minimize the tax burden, however, management must understand the interrelationship between business operations and the tax liability. A chart was first developed as a testing device for an advanced accounting course. Since students performed so poorly on the question it was later utilized successfully as a teaching aid-originally in an advanced course and subsequently in a tax course.